Trafficking in the post pandemic: casting human security, and universal periodical review in Malaysia - Ravi Mahalingam,; Adilah Abdul Ghapor,; Rudy Kana, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Growing research interest and policymaking over the issue of Malaysian security and the human dimension of threats have brought transdisciplinary and transnational engagements in the problem of trafficking. Unpacking salient rudimentary attributes of trafficking, human security, and humanitarian and human rights improvement can no longer be treated as ivory tower work per se. There is a continuous need to accommodate constructive space for academics, policymakers, and state and non-state actors in the idea exchange of the input and output-processes of our national security policy. This note provides an overview of our editorial work and selection of articles for the publications of this special issue. We remained indebted to the relevant ministries, universities, funding bodies, and non-governmental organisations involved throughout the research and publication process